George’s Island, Labrador - A high-density predator-free refuge for a woodland caribou subpopulation? - Jeffery, Rebecca A.; Otto, Robert D.; Phillips, Frank R. (Rangifer, 2007)
The movement patterns and demographic parameters were measured for caribou (Rangifer tarandus caribou) on George’s Island (Labrador, Canada) to determine if the population is separate from the Mealy Mountain Caribou Herd. Movements between George’s Island caribou and nearby Mealy Mountain caribou were examined through satellite telemetry (April 2005 to April 2006). Demographic information was collected through aerial classification surveys. The predator-free island is currently maintaining a density of 22.5-26.5 caribou/km2. Female survival appears high and the recruitment rate in late fall-early spring was 19.0-29.2% calves. Mainland caribou moved very little throughout the year, travelling no more than 53.7 km on average from their initial collaring locations. Also, satellite data indicated no mixing between animals on George’s Island and the mainland. The elevated caribou density and high proportion of calves suggest that George’s Island could at times be acting as a predator-free recruitment area and that George’s Island may be a subpopulation from which animals disperse to the mainland.